Pengaruh Jumlah UMKM dan Modal UMUM terhadap Pertumbuhan Ekonomi di Kabupaten Brebes - Dewi Safitri; Titi Rahmawati; Dumadi; Maftukhin; Nur Afridah (Journal of Accounting and Finance (JACFIN), 2020)
Micro, small and medium enterprises (MSMEs) are one of the business sectors that can grow and develop in the economy in Brebes. MSMEs are a good place to create jobs planned by both the government, the private sector and individual businesses. This research is a descriptive research with a quantitative approach that uses primary data as a source of data. Data collection techniques in the form of field research (field research). The purpose of the study is to analyze the influence of the number of MSMEs and MSME capital on economic growth in Small Medium Enterpreses activities in Brebes both partially and simultaneously. The data analysis techniques used in this study are classical assumption analysis and multiple linear regression. Hypothesis testing using multiple linear regression analysis, with the help of the SPSS program. The results of the study simultaneously showed that the number of MSMEs had a positive influence and a significant value of 0.00 > 0.005 and the influence of MSME capital had a positive influence and a significant value of 0.00 > 0.005 on the economic growth of Small Medium Enterpreses activities in Brebes. The results of the persial test show that the influence of the number of MSMEs and MSME capital has a significant effect on the economic growth of Small Medium Enterpresses activities in Brebes.